Comparing traits of native and alien plants: Can we do better?. (26th September 2017) - Hulme, Philip E.; Bernard‐Verdier, Maud
Abstract: A frequent question in invasion ecology is whether the traits of alien plant species differ from natives. This question is increasingly addressed at the plant community scale to assess the role trait differences play in community assembly. Nevertheless, there remains considerable debate as to the value of native vs. alien trait comparisons. Recommendations are made to address seven conceptual and methodological limitations in current approaches used to assess trait differences between native and alien plants: account for spatial scale dependence, make an informed choice of traits, evaluate multiple trait dimensions, incorporate intraspecific trait variation, use appropriate null models, examine environmental gradients, and assess temporal variation in trait spectra. Tackling these limitations will dramatically improve the value of native vs. alien trait comparisons. Traits should be selected based on expectations of abiotic and/or biotic constraints. Phylogenetic distances can provide valuable insights but are no substitute for the measurement of individual traits when contrasting alien and native species. An ideal set of traits would include one or more leaf, stem, seed and root traits as well as flowering phenology and plant height at maturity. Comparisons of intraspecific trait variation among native and alien species within the same plant community are rare but could improve predictions of interspecific competition and the response of communities to plant invasions. The full plant community should be examined rather than selected species subsets and comparisons between native and alien species traits are better undertaken at a neighbourhood scale. The frequency distribution of alien and native species traits may change over time through competitive exclusion as well as contemporary evolution. Repeated surveys of species abundances and traits are required to understand the consequences of trait differences between aliens and natives for plant community assembly. Analyses of the role of species traits in plant invasions need to quantify differences in a priori identified traits within communities along suitable environmental gradients and test hypothetical trait patterns against appropriate null expectations. The infrequent application of such approaches may explain the limited generalisations regarding the role of trait differences between native and alien species in the invasion of plant communities. A plain language summary is available for this article. Abstract : Plain Language Summary